Clinical and Pharmacological Importance of Micronutrients for Pregnant Women and Newborns - Rasulov Saydullo Kurbanovich; Rustamova Kh. Kh; Narmetova S. Ya (International Journal on Integrated Education, 2022)
The aim of the study was to study the micronutrient composition and the physiological role of the national product - grape gurob, in order to provide nutritional support, correction and prevention of macro- and microelement deficiencies in the "Mother-child" system. To prevent micronutrient deficiencies in the "Mother-Child" system, the macro- and microelement composition of little-studied and little-used national food products - grape gurob - was studied. The determination of 23 macro- and microelements in the composition of the grape gurob was carried out by the neutron activation method, bacteriological, toxicological, radionuclide studies were carried out. The composition of the grape gurob revealed a high concentration of macro- and microelements - potassium, calcium, magnesium, sodium and chlorine, as well as essential microelements - iron, zinc, copper, cobalt, manganese, iodine and molybdenum. Grape Gurob should be recommended for the purpose of preventing and correcting micronutrient deficiencies, optimizing the growth and development of children, accelerating recovery processes and improving the quality of life in the Mother-Child system.